Optimization of Fluorescence In Situ Hybridization technique for analyzing microorganisms involved in bioprocesses - Pérez, Marina González (2016)
This work is focused on FISH technique optimization for yeast and bacteria analysis, by enhancing the FISH signals by increasing the number of fluorescent cells and their fluorescence intensities. With this aim different fixation procedures and hybridization conditions were tested. The modifications introduced in the procedure represent an important contribution for FISH optimization.